2015
DOI: 10.1213/ane.0000000000000996
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of the Novel Peripheral Analgesic Isovaline as an Adjuvant to Propofol for General Anesthesia and Conscious Sedation

Abstract: The novel analgesic, isovaline, coadministered with propofol, produced general anesthesia and conscious sedation in mice. The margin of safety for propofol-isovaline was considerably higher than that for propofol-fentanyl. This study's results show that propofol-based sedation and general anesthesia can be effectively and safely produced by replacing the conventional opioid component with a brain-impermeant peripherally acting γ-aminobutyric acid type B receptor agonist. The results provide proof of the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In a previous animal study, hypnosis was defined as the inability of a supine mouse to turn upright from sternal recumbency (loss of righting reflex) and the absence of response to light touch (gentle pinch at the hind paw). 10 Since the animals' heads were in a head restraint in our study, we were only able to define hypnosis by the absence of a response to light touch. The respiratory and circulatory responses during administration of propofol were not monitored during the experiment, although all mice recovered from anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous animal study, hypnosis was defined as the inability of a supine mouse to turn upright from sternal recumbency (loss of righting reflex) and the absence of response to light touch (gentle pinch at the hind paw). 10 Since the animals' heads were in a head restraint in our study, we were only able to define hypnosis by the absence of a response to light touch. The respiratory and circulatory responses during administration of propofol were not monitored during the experiment, although all mice recovered from anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…The up and down procedure was used in the loss of righting reflex (LRR) assay to determine ED 50 of sedation [20]. The LRR for more than 10 s was regarded as positive for sedation; otherwise, the observation was regarded as negative [21].…”
Section: Righting Reflex Testmentioning
confidence: 99%
“…Our laboratory has focused on an unusual analgesic prototype, isovaline, a small amino acid that activates peripheral GABA B and group II metabotropic glutamate receptors to produce antinociception. Isovaline has no apparent adverse effects following systemic or central administration in various murine pain models (Lim & Lee, ; MacLeod et al., ; Whitehead et al., ; Asseri, Puil, Schwarz, & MacLeod, ; Whitehead et al., ). Furthermore, structure–activity relationship (SAR) studies of isovaline revealed that the amino acid, 1‐amino‐1‐cyclobutanecarboxylic acid (ACBC), produces antinociceptive effects in the formalin foot assay (Fung et al., ).…”
Section: Introductionmentioning
confidence: 99%